2020
DOI: 10.1007/978-3-030-63467-4_23
|View full text |Cite
|
Sign up to set email alerts
|

IoT Based Crop-Field Monitoring and Precise Irrigation System Using Crop Water Requirement

Abstract: Existing practices of crop irrigation is manual and based on generic traditional recommendations. Crops when provided lesser water, shows reduced growth and reduced uptake of calcium. Excessive irrigation leads to root death and water wastage. Hence, irrigating crops with precise water becomes an important problem. Towards this objective, an IoT based crop field monitoring and precise irrigation system is proposed that monitors crop-field and computes precise crop water requirement based on its life cycle and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Recently, SMS applied to irrigate pear orchards were found to save 50% of applied irrigation water while maintaining good crop production and quality (Hamouda et al, 2021). In a study carried out by Rajaram and Sundareswaran (2020), SMS were used for precision irrigation of brinjal plants, where the quantity of water needed was calculated based on the temperature and humidity obtained from the probes. The results indicated that 53% of water has been saved from wastage.…”
Section: Smart Strategies For Precision Irrigationmentioning
confidence: 99%
“…Recently, SMS applied to irrigate pear orchards were found to save 50% of applied irrigation water while maintaining good crop production and quality (Hamouda et al, 2021). In a study carried out by Rajaram and Sundareswaran (2020), SMS were used for precision irrigation of brinjal plants, where the quantity of water needed was calculated based on the temperature and humidity obtained from the probes. The results indicated that 53% of water has been saved from wastage.…”
Section: Smart Strategies For Precision Irrigationmentioning
confidence: 99%